Comparison of Interleukin-6 Levels After Rectal Irrigation With Metronidazole and Normal Saline Versus Normal Saline Alone in Male Wistar Rats With a Hirschsprung-Associated Enterocolitis Model - Agung Aditya Arnaya; Kadek Deddy Ariyanta; Ketut Sudartana (Universitas Ahmad Dahlan, 2026)
Background: Hirschsprung-Associated Enterocolitis (HAEC) is a serious complication of Hirschsprung disease characterized by intestinal inflammation. Rectal irrigation with systemic antibiotics is the standard management, but efficacy remains limited. Metronidazole, an effective anaerobic antibiotic, has immunomodulatory properties that may reduce inflammation. This study evaluates whether topical metronidazole combined with normal saline irrigation reduces IL-6 levels more effectively than saline alone. Method: An experimental study using 20 male Wistar rats (2-3 months, 250-300g) was conducted. HAEC model was induced using benzalkonium chloride (BAC) 0.1% applied topically to the sigmoid colon. Rats were randomized into two groups: Control group (K) receiving rectal irrigation with normal saline 0.9% (10 mL/kg/day, once daily), and Treatment group (P) receiving combination irrigation with metronidazole 7.5 mg/kg/day plus normal saline 10 mL/kg/day (twice daily). Both interventions began on day 7 post-induction and continued until day 14. Serum IL-6 levels were measured by ELISA on day 14. Data were analyzed using independent samples t-test. Results: The combination group demonstrated a mean IL-6 level of 4.47 ± 1.54 pg/mL versus 5.63 ± 2.04 pg/mL in the saline-only group (mean difference -1.15 pg/mL, 95% CI: -2.85 to 0.54; t = -1.430, df = 18, p = 0.170). Normal distribution was confirmed in both groups (Shapiro-Wilk: W = 0.904, p = 0.243 and W = 0.879, p = 0.126, respectively), and homogeneity of variance was confirmed by Levene’s test (F = 0.043, p = 0.837). Conclusion: Combination irrigation with metronidazole demonstrated a numerically lower mean IL-6 level compared with saline alone (4.47 ± 1.54 vs. 5.63 ± 2.04 pg/mL; Cohen’s d = 0.64); however, this difference was not statistically significant under the current experimental conditions (p = 0.170). Given the unequal irrigation frequency between groups and the limited statistical power of this pilot study, these findings should be regarded as hypothesis-generating rather than evidence of therapeutic efficacy, warranting larger, adequately powered trials with equal irrigation frequency and longer intervention duration.